IMPLEMENTASI DATA FORWARDING SERVER DALAM PENGELOLAAN DATA UGM COCOA TEACHING AND LEARNING INDUSTRY, BATANG, JAWA TENGAH - Kusuma, Enas Dhuhri; Suwastono, Addin; Yesmin Pebrianto, Della (Bapelitbang Kabupaten Batang, 2024)
UGM Cocoa Teaching and Learning Industry (CTLI) is a factory owned by UGM that focuses on processing cocoa beans, located in Batang Regency, Central Java. Apart from that, CTLI also has a role as a research and innovation institution with the aim of finding new knowledge and technological breakthroughs in the cocoa industry. In processing cocoa beans, CTLI uses high-tech machines so that the data on the machine can be recorded. At its inception, CTLI subscribed to the Mindsphere service from Siemens to collect and manage data so that data could be stored properly in the factory database. But currently, CTLI has stopped the Mindsphere subscription so that production data cannot be saved into the database. In order to overcome this problem, the OPC UA communication protocol was used to obtain data from the factory system and forward the data using Node-RED which was then stored in the factory database. This database is local and stored on the CTLI PC so that accessing it remotely can be done using Anydesk. Data that has been stored in the database can be used to develop and optimize CTLI operations in the future.